A Story of South-East Asian TESOL Why Teach Abroad: Its Opportunities and Challenges - Luthfi Nicola Sereni; Elih Sutisna Yanto (Universitas Pendidikan Mandalika, 2021)
This study aimed to investigate a story from a South-East Asian TESOL teacher. The purpose of this study is to inspire and guide in-service and pre-service English teachers to teach EFL/ESL overseas either to native English-speaking or non-native English-speaking countries. The participant of the study is a BA TESOL Teacher from the Philippines teaching English in the Kingdom Saudi of Arabia. The data were collected through a semi-structured interview and analyzed through Braun & Clarke’s thematic analysis. The data then will be coded, read multiple times, and themes were assigned and generated. The findings describe that teaching abroad provides better prosperity and additive and transformative development for the teachers. However, teachers that aim to teach abroad should be globally accepted and possess proper identity and agency to overcome culture shock, language differences, homesickness as the common challenges of teaching abroad. Overall, teaching abroad should be considered greatly by teachers who are interested to receive a higher salary and involved various teachers’ development experience.